REPRESENTASI PEREMPUAN DALAM FILM “BERBAGI SUAMI” (ANALISIS SEMIOTIKA ROLAND BARTHES) - Zulaikha Rumaisha Alwi (Jurnal Visi Komunikasi, 2021)
The Woman repesentation in "Sharing Husband" movie is the title of this research.  The problem of this research was to know about how the media's repesentation of the woman in the movie. The aim of this research was stated on the research problem it was to  know about how the media's repesentation of the woman in the movie. This research is qualitative  descriptions research used semiotic    model by Roland. The data was collect from the movie scene which is has the media repesentation of the woman on the movie. The data were  analyzed  used semiotic mode by Rolland. the data were analyze into two steps, the denology analyses  was the first step, on this step the actuall meaning of the scene are being analyze. The second step is Conotation analyses , this step the research analyze the Meaning of the scenes that reperesented by the media. The result of this reearch is from the movie " sharing husband", the media was represented the lives of three women as a mother and as the wife. As the mother with a full of love and erudite. And the lonely, innocent , and a shy wife. And the matrealistic wife. The three stories was packed inbthe movie with a different message in every scene